Model ADDIE dan Waterfall sebagai framework pengembangan media pembelajaran (studi kasus: media pembelajaran sistem peredaran darah) - Rustandi, Andi; Darmawati , Darmawati (Jurnal Ilmiah Teknologi Informasi Asia, 2025)
The ADDIE model, while effective for instructional design, often lacks a structured approach to the technical aspects of software development. This study introduces a combined ADDIE-Waterfall framework to create learning media that are both pedagogically effective and technically sound. Using a Research and Development (R&D) method, a learning application for the high school biology topic of the circulatory system was created. The product was evaluated for feasibility through expert validation, practicality through user response questionnaires (n=150), and effectiveness using pre-test and post-test scores to calculate a normalized gain (N-Gain) score. The results demonstrated high quality, with an expert validation score of 92% (“Very Feasible”) and a user response score of 95% (“Very Good”). The learning media were also effective, showing a significant improvement in student learning outcomes with an N-Gain score of 0.63, indicating moderate effectiveness. The findings confirm that integrating the ADDIE and Waterfall models provides a comprehensive framework for developing high-quality, effective educational software. This combined approach successfully addresses both instructional and technical requirements, resulting in a product that is well-received by users and improves learning.